1978
DOI: 10.1111/j.1432-1033.1978.tb12138.x
|View full text |Cite
|
Sign up to set email alerts
|

Physico‐Chemical Properties of Phosphatidylglycerol in Membranes of Acholeplasma laidlawii

Abstract: Membranes isolated from Acholeplusma luidlawii B grown on palmitic acid, elaidic acid, oleic acid or linoleic acid have been treated with excess phospholipase A2 at different temperatures. Hydrolysis of phosphatidylglycerol only occurs at temperatures above the onset of the gel to liquid-crystalline phase transition of the lipids as measured by differential scanning calorimetry. The extent of phosphatidylglycerol hydrolysis as a function of the temperature reflects the phase transition of this phospholipid in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

1979
1979
1993
1993

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Protection against phospholipase A, action can also occur when the lipids are present in the highly ordered gel state as we have previously shown (20,21). Membranes of A. laidlawii grown on oleic acid do not show a gel-to liquid-crystallinephase transition in the temperature range from 0 to 4O"C, indicating that the lipids in this membrane are in the liquid-crystalline state.…”
Section: Resultsmentioning
confidence: 75%
See 2 more Smart Citations
“…Protection against phospholipase A, action can also occur when the lipids are present in the highly ordered gel state as we have previously shown (20,21). Membranes of A. laidlawii grown on oleic acid do not show a gel-to liquid-crystallinephase transition in the temperature range from 0 to 4O"C, indicating that the lipids in this membrane are in the liquid-crystalline state.…”
Section: Resultsmentioning
confidence: 75%
“…The significance of these boundary lipids in membrane function is suggested by studies which have shown that the activities of some membrane enzymes are dependent upon the presence of certain types of lipids (4,(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) report, evidence is obtained by using phospholipase accessibility as the criterion to detect the existence of boundary lipids in Acholeplasma laidlawii membranes. In A. laidlawii membranes, phosphatidylglycerol is one of the major lipids and can be hydrolyzed by exogenous phospholipase (20,21). Studies with pancreatic phospholipase A, have shown that the fatty acid composition of this phospholipid and the incubation temperature are important parameters which determine both the rate and the extent of hydrolysis.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It was not observed after direct insertion of the probe in the membrane (Dupou et al, 1988). In addition, a number of studies have indicated the presence of lipid pools which are inaccessible to phospholipases (Bevers et al, 1978). It has also been shown that exogenous lipids do not intermix freely with the major pool of endogenous lipids (D'Souza et al, 1983).…”
Section: Discussionmentioning
confidence: 99%
“…Phosphatidylthioglycerol provides a means for conveniently determining the dynamics of phosphatidylglycerol in bilayer systems. The localization of phosphatidylglycerol has been investigated in the membrane of Micrococcus lysodeikticus and Acholeplasma laidlawii by using combinations of lipid transfer proteins and phospholipases (Barsukov et al, 1976;Bevers et al, 1978) and in bacteriophage PM2 by reaction with sulfanilic acid diazonium salt (Schafer et al, 1974). Studies of the distribution of this lipid in unilamellar liposomes have been briefly reviewed by Lentz et al (1980), who used periodate oxidation followed by chemical determination of released formaldehyde to quantify accessible phosphatidylglycerol.…”
Section: Discussionmentioning
confidence: 99%